High selective hydrocarbon and hydrogen products from catalytic pyrolysis of rice husk: Role of the ordered mesoporous silica derived from rice husk ash for Ni-nanocatalyst performance - Pham, Le Kim Hoang; Alsaiari, Mabkhoot; Thao, Bui T. Thu; Hieu, Nguyen Huu; Phuc Hoang Duy, Nguyen; Vo, Dai-Viet N.; Witoon, Thongthai; Nguyen, Van Cuong; Kongparakul, Suwadee; Samart, Chanatip; Trinh, Thanh H.; Al-Gheethi, Adel (Elsevier Ltd., 2024)
This study successfully synthesized ordered mesoporous silica using a sodium silicate solution derived from high-purity silica extracted from rice husk (98.09%), aiming to catalyst support for integrating fast catalytic upgrading of rice husk. The ordered mesoporous silica, including MCM-41 and KIT-6, were synthesized by co-assembly with additional surfactants, consisting of Cetyl trimethylammonium bromide (CTAB) and Pluronic P123, respectively. A series of 10 wt.% Ni on MCM-41 (Ni/HMS1) and KIT-6 (Ni/HMS2) were synthesized via ethylene glycol ultrasound-assisted wetness impregnation, which enhanced bio-oil quality by reducing oxygen compounds. This method also improved NiO reducibility up to 91.41%, with nickel phyllosilicate playing a pivotal role in preventing Ni-metallic sintering during the reduction process. The well-dispersed small Ni particles yielded high Ni performance in deoxygenation. Moreover, the order of pore size and structure of the hexagonal nanochannel structures influenced the selective hydrocarbon products in bio-oil. Ni/HMS1, with smaller pore sizes (3–5 nm), achieved a balanced hydrocarbon composition with aromatic (44.91%) and aliphatic (15.65%) components, while Ni/HMS2, having larger pores (8–10 nm), predominantly contained aromatic hydrocarbons (67.45%). The utilization of a green methodology for extracting high-value silica from biological sources promises to innovate and boost eco-consciousness in all rice husk pyrolysis products.